DEVELOPMENT AND VALIDATION OF E-TOOLSIM CAKRA AS AN INTERACTIVE SIMULATOR FOR LEARNING AUTOMOTIVE EQUIPMENT - Andika Bagus Nur Rahma Putra; Mahfudi Sahly Subandi; Rochmawati Rochmawati; Nurul Ulfatin; Tee Tze Kiong (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The aim of this research is to design and test the development of e-ToolSim Cakra as an interactive learning media for learning automotive tools at Automotive Engineering Education Program (AEP) Universitas Negeri Malang. The research of this experiment was conducted through Research and Development (R&D) model which consisted of analysis, design, development, implementation, and evaluation (ADDIE) model. The subjects consisted of 3 experts in their fields, 2 experts in media and 25 students as users. Aiken’s V was used to analyze the data on validity and descriptive percentage was used for practicality. In the present study expert validation sheets and the student response questionnaires were used. The result of the media validity test is the aspect of content with a mean score of Aiken’s V by 0.85 and the aspect of media by 0.86, which means that the e-ToolSim Cakra is a valid learning media to use because the mean value of the Aiken’s V score is greater than 0.8. The results of trials with students indicated that the practicality level was 83.5% which was very appropriate. The results can be used as a medium that can be applied as pedagogy in theory and practice gap filling that uses simulators as a medium in interactive procedure simulation. The conception of simulation based learning was then developed, in conjunction with the product and was broken down into four phases: theorisation, simulation, practice and reflection. Therefore, the prototype of e-ToolSim Cakra which was obtained can be used as the learning medium in automotive equipment. The present research paper contributes towards the interactive simulation based vocational learning development integrated with the digital system.